ASSOCIATIVE SOCIAL INTERACTION; HARMONY RELATIONSHIP OF MUSLIMS WITH SAPTA DARMA PEOPLE : INTERAKSI SOSIAL ASOSIATIF; POTRET HUBUNGAN KERUKUNAN UMAT MUSLIM DENGAN PENGANUT SAPTA DARMA - M Thoriqul Huda; Moh. Sholeh Afyuddin (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
Humans are social beings who in carrying out life always depend on others, mutually beneficial social interaction isan effort that must be made by each individual to meet all the necessary needs, even if they have to interact withother individuals of different religions. This study seeks to see the social interaction of the Muslim community withadherents of the Sapta Darma belief in Pare Kediri. By using a qualitative approach, the researcher will conduct directobservations in the field in order to explore the model of social interaction relationships that occur. The results of thestudy show that the Muslin and Sapta Darma communities build social interactions with an associative model, wheresocial relations occur with mutual benefit, so that a harmonious and harmonious relationship is created, besides thatthe two groups also build inclusive theology as a basis for building inter-religious relations. and lastly, tradition playsan important role as a field of harmony in social interaction.